The effect of entry on R&D networks. (24th August 2018) - Petrakis, Emmanuel; Tsakas, Nikolas
Abstract: We investigate the effect of potential entry on the formation and stability of R&D networks considering farsighted firms. The presence of a potential entrant often alters the incentives of incumbents to collaborate. Incumbent firms may form an otherwise undesirable collaboration to deter entry of a new firm. Moreover, an incumbent may refrain from establishing an otherwise desirable collaboration, expecting to form a more profitable link with the entrant. Finally, potential entry may lead an inefficient incumbent to exit the market. Welfare analysis shows market and social incentives to be often misaligned. We propose a subsidy scheme that encourages welfare‐improving entry.